Effect of polyphenols supplemented canola meal based diet on growth performance, nutrient digestibility and antioxidant activity of common carp (Cyprinus carpio Linnaeus, 1758) fingerlings - Hussain, Syed Makhdoom; Gohar, Hina; Razul, Azhar; Shahzad, Muhammad Mudassar; Akram, Afia Muhammad; Tariq, Muhammad; Hussain, Majid; Ali, Mukthar; Khhalid, Anam (Indian Journal of Fisheries, 2020)
A 70-days feeding trial was conducted to assess the impact of polyphenols supplemented canola meal based diets on growth performance, nutrient digestibility and antioxidant activity of common carp (Cyprinus carpio Linnaeus, 1758) fingerlings. Seven experimental diets viz., T0, T1, T2, T3, T4, T5, T6 and T7 with graded levels of polyphenols at 0, 100, 200, 300, 400, 500 and 600 mg kg-1 respectively were formulated. Each treatment diet was fed to fishes in triplicate tanks and in each replicate, fifteen fingerlings were stocked. Effect of each treatment on the weight gain, feed conversion ratio (FCR), specific growth rate (SGR), nutrient digestibility and antioxidant activity were assessed. Maximum growth performance, highest SGR (1.41) and best FCR (1.31) was observed in fish fed test diet T4 having 400 mg kg-1 of polyphenols. Nutrient digestibility in terms of crude protein (72%), crude fat (76%) and gross energy (67%) also significantly increased (p<0.05) by supplementation of polyphenols at 400 mg kg-1 level. With respect to antioxidant activity, increasing trend was observed with increasing levels of dietary polyphenols with the highest antioxidant activity recorded in fish fed T6 diet supplemented with 600 mg kg-1 of polyphenols. Keywords: Common carp, Lipid oxidation, Nutrients digestibility, Phenolic compounds, Weight gain